Networks of hyperbolic balance laws - Borsche, Raul (My University, 2017)
Models with networks of hyperbolic balance laws are currently used for several applications, e.g. river flows, the human circulatory system, gas pipelines or road networks. These motivations triggered a constant development of analytical results as well as numerical methods. This talk aims to provide an overview of the developments in the past years with a focus on the construction of suitable numerical schemes. Additionally a possible extension to non-conservative equations will discussed.
Keywords: Modelización; systems of conservation laws; Networks; Coupling conditions; Shallow water models